The Persistence of Capital Account Crises - Mecagni, Mauro; Atoyan, Ruben; Hofman, David (Washington, D.C. : International Monetary Fund, 2009)
This study contributes to the literature on capital account crises in two ways. First, our analysis of crisis episodes between 1994 and 2002 establishes a clear relationship between the persistence of crises, their complexity, and the intensity of movement of key macroeconomic variables. Second, we provide a systematic examination of the determinants of crisis duration. Our econometric analysis suggests that initial conditions and the external environment plays a key role in determining crisis persistence. The policy response also matters, but cannot offset a record of poor past policies. Overall, the results underscore the critical importance of crisis prevention efforts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet